Making your meetings productive - Andres, Tomas Quintin D.; Reyes, Gracianus R. (Quezon City New Day, 1998)
This book will guide you to organize, plan and control productive meetings. It will help you lead more effective meetings by adding interest, clarity and direction. It gives you the keys to plan and run productive, focused meetings that really work.
Keywords: Meetings -- Handbooks, manuals, etc